PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, SANKSI WAJIB PAJAK DAN SISTEM SAMSAT DRIVE THRU TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Hendrianto, Samino; Masturo, Masturo; Dara, Nursimah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
ABSTRACT The purpose of this study was to determine the effect of taxpayer knowledge, taxpayer awareness, taxpayer sanctions, and the Samsat Drive Thru system on motor vehicle taxpayer compliance (Empirical Study on Motorized Vehicle Taxpayers Samsat Kelapa Dua SDC Serpong). The population of this study includes all registered taxpayers at Samsat Kelapa Dua SDC Serpong. The sampling technique used was the Quota Sampling Technique. Based on the predetermined criteria obtained 100 respondents. The type of data used is primary data obtained from the results of the questionnaire. The analytical method used is multiple linear regression analysis. The results of the study partially show that Taxpayer Knowledge and Taxpayer Sanctions have an effect on Motor Vehicle Taxpayer Compliance, while Taxpayer Awareness and the Samsat Drive Thru System have no effect on Motor Vehicle Taxpayer Compliance. Simultaneously all independent variables affect the dependent variable. Keywords : Taxpayer Knowledge, Taxpayer Awareness, Taxpayer Sanctions, Samsat Drive Thru System, Motor Vehicle Taxpayer Compliance